New species of Lentulidae and Tettigoniidae (Orthoptera) from the Udzungwa Mountains, Tanzania - Hemp, Claudia (Zootaxa, 2017)
A list of the Caelifera and Ensifera (Orthoptera) of lowland wet forest of the Udzungwa Mountains is presented. Five new species are described. These are the Agraeciini Afroagraecia mangula n. sp. (Conocephalinae), the Meconematinae Afrophisis undosa n. sp. and Phlugidia ampendiculata n. sp., the Phaneropterinae Eurycorypha pianofortis n. sp., and the lentulid Usambilla castigata n. sp. A total number of 19 Caelifera and 26 Tettigoniidea species are recorded. About one third of the species are endemic to the Udzungwa Mountains.